Forming a set of alternate variants of transport and technological container cargo delivery systems - Наумов, Віталій Сергійович; Потаман, Наталя Володимирівна; Вітер, Наталя Сергіївна (Eastern-European Journal of Enterprise Technologies, 2013)
Transport and technological system of cargo delivery in containers is a complex system of interacting elements, so for solving the problems of planning the delivery systems structure it is appropriate to use the methods of system analysis, the essence of which lies in identifying the relationships between research object components and in estimating the effect of each component on a whole system functioning. To solve the problem of forming a set of delivery system structures it is necessary to preliminarily analyze the available transport market participants, which may be involved in the delivery of the cargo consignment. The proposed method provides a complete set of alternative patterns of delivery system for a given market situation, taking into account the geographical parameters of orders for containers delivery. The paper presents the theoretical basis for the formation of the complete set of alternative cargo delivery systems. Examples of the proposed methodology application for the formation of alternative sets of containerized cargo delivery systems have been given in the article. The necessity of using the proposed approach in solving the problem of choosing the optimal cargo delivery variant has been shown.